Epidemiology of injuries in men's professional lacrosse among 158 athletes in a single season - Tyler S. Warner; Patrick S. Buckley; Catherine A. Logan (Journal of Cartilage & Joint Preservation, 2022)
ABSTRACT: Background: Injury rates and patterns in men's professional lacrosse are not well known. Objectives: To define the injury rates and patterns which occur in men's professional lacrosse. Methods: Injury data were collected during the inaugural season of a men's professional lacrosse league. Player demographics, including age, height, weight, team, games played, and position were recorded. Injuries were detailed by type (contact v noncontact), field surface (turf v grass), timepoint within the season, and location on the body. Results: The overall injury rate over the course of a professional lacrosse season was 43.87% (68/155). Three players (1.9%) underwent surgery and 2 players (1.2%) sustained season-ending injuries. There was no significant difference between injured and noninjured players on the basis of age, height, weight, field surface, and position played. There was a statistically significant difference in noninjured and injured players based on total games played (7.8 vs 10.9 games, P < .001, odds ratio 1.3, 95% CI 1.17–1.47). Athletes playing in more games had a higher risk of sustaining an injury, compared to athletes playing in fewer games. Forty-six percent of all injuries reported involved the lower extremity and 35% involved the upper extremity. Conclusion: Slightly less than half of all professional lacrosse athletes reported an injury over the course of the season; however, season-ending injuries and injuries necessitating surgery were rare.